How do women maximize the value of mentorship? Insights from mentees, mentors, and industry professionals. Issue 2 (15th January 2020) - Read, Dustin C.; Fisher, Patti J.; Juran, Luke
Abstract : Purpose: The purpose of this paper is to explore the perceptions of women working in the commercial real estate industry to assess how they approach mentoring relationships and take steps to maximize the value derived therefrom. Design/methodology/approach: Through thematic analysis of 39 interviews conducted with women serving as local chapter presidents of CREW Network, the paper offers insights as to how women position themselves to receive mentorship throughout their careers and engage with mentors to address their evolving needs. In particular, three themes of commitment, reciprocity in the mentoring relationship and mentee motivation emerged. Findings: The results suggest that this is a strategic process and one in which many women are proactively engaging to ascend to leadership positions in the corporate world. While the study is limited to those working in commercial real estate, clear implications exist for other industries. Originality/value: By identifying and exploring these themes, the paper serves as a starting point for future research considering how women inside and outside of the commercial real estate industry can more strategically pursue mentorship and use it to attain leadership roles.